The correlates between students' sociodemographic and socioeconomic background factors and level of academic achievement: a case of UiTM Kampus Kuala Pilah students / Akashah Afiq Azmer, Mohd Nazir Rabun and Muhammad Syakir Md Shazali - Azmer, Akashah Afiq; Rabun, Mohd Nazir; Md Shazali, Muhammad Syakir (Universiti Teknologi MARA, 2021)
Student's academic achievement is one of the aspects that has been the focus and commitment of Universiti Teknologi MARA (UiTM) especially for Bumiputera students. The academic achievement is vital for the institution to be regarded as the quality of higher education provider in Malaysia standing tall among other local universities. This study examined the correlation between students' sociodemographic and socioeconomic background factors and level of academic achievement in UiTM Kuala Pilah campus, Negeri Sembilan. A cross-sectional survey on 144 undergraduates in UiTM Kuala Pilah was engaged and employed for this study. The correlation between sociodemographic (family size, parents' education & place of residence) and socioeconomic background factors and level of student's academic achievement were thoroughly examined and analyzed. The outcome of this study revealed that socioeconomic status was found to have significant positive correlation to the level of student's academic achievement. The substantive results of this study will furnish information to the government and relevant parties, such as the (HEIs) (Higher Learning Institutions) to devise the strategies in dealing with the issue of students' academic achievement. There are needs to put a greater emphasis regarding the disadvantaged students who are facing difficulties to have quality education in university while at the same time planning to sustain the student's welfare